The Effects of Aloe vera Gel, Sesame Oil and Camphor Oil on Pseudomonas aeruginosa Isolated from Burnt Patients - T. Flayyih, May; Q. Majeed, Raghad (Iraqi Journal of Pharmaceutical Sciences, 2017)
Three isolates of P. aeruginosa were isolated from burnt patients. The ability of these isolates for adhesion and formation of slime layer were tested, the result showed that all isolates were able to adherence on the smooth surface. The sensitivity of P. aeruginosa isolates for antibiotics were tested , all isolates were sensitive to Gentamycin, Piperacillin and Amikacin Ciprofloxacin, and resist to Tetracyclin, Amoxicillin, Cephalexine , Ceftriaxone. Ciprofloxacin and Amikacin were found effective against P. aeruginosa isolates with MIC values of 3.8 Î¼g/ ml for Ciprofloxacin and 0.244 Î¼g/ ml for Amikacin The antibacterial effect of Different concentrations of Aloe vera gel, Sesame Oil and Camphor Oil against P. aeruginosa were determined, Camphor was highly effective with Concentration inhibit bacteria value of 10% followed by Sesame Oil (20%) and Aloe vera gel (>75%). The combinations of Aloe vera gel, Sesame Oil and Camphor Oil and antibiotics (Ciprofloxacin and Amikacin ) showed that the efficacy of the two antibiotics (Ciprofloxacin and Amikacin ) against P.aeroginosa isolates was improved in the presence of Aloe vera gel, Sesame Oil and Camphor Oil.Key words : Aloe vera gel, Sesame Oil , Camphor Oil , Pseudomonas aeruginosa.